2022
DOI: 10.1186/s10020-022-00545-x
|View full text |Cite
|
Sign up to set email alerts
|

PACS-2 deficiency in tubular cells aggravates lipid-related kidney injury in diabetic kidney disease

Abstract: Background Lipid accumulation in tubular cells plays a key role in diabetic kidney disease (DKD). Targeting lipid metabolism disorders has clinical value in delaying the progression of DKD, but the precise mechanism by which molecules mediate lipid-related kidney injury remains unclear. Phosphofurin acidic cluster sorting protein 2 (PACS-2) is a multifunctional sorting protein that plays a role in lipid metabolism. This study determined the role of PACS-2 in lipid-related kidney injury in DKD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…HFD and STZ combination is a well‐known approach for studying diabetic nephropathy 25,26 . A total of 30 four‐week‐old male C57BL/6 mice were purchased from Hunan SJA Laboratory Animal Co. Ltd. (Hunan, China).…”
Section: Methodsmentioning
confidence: 99%
“…HFD and STZ combination is a well‐known approach for studying diabetic nephropathy 25,26 . A total of 30 four‐week‐old male C57BL/6 mice were purchased from Hunan SJA Laboratory Animal Co. Ltd. (Hunan, China).…”
Section: Methodsmentioning
confidence: 99%
“…In studies involving streptozotocin-induced diabetic mice and DKD patients, reduced levels of PACS-2 expression have been observed. Notably, diabetic tubule-specific Pacs-2 deletion accentuates lipid synthesis through upregulated sterol O-acyltransferase 1 (SOAT1) expression and concurrent inhibition of cholesterol efflux ( 87 ). This intensified lipid accumulation in tubular cells contributes to the progression of albuminuria excretion and exacerbates kidney damage.…”
Section: Mechanisms Of Renal Tubular Injuries In Dkdmentioning
confidence: 99%
“…The study by Chen et al found that inhibition of DsbA-L expression aggravated lipid deposition in DKD, and activation of the AMPK pathway is a potential mechanism by which DsbA-L plays a role in renal lipid deposition 110 . Zhao et al found that diabetic mice with proximal tubule PACS2-specific knockout had more severe tubular damage and proteinuria than controls, which was accompanied by increased lipid synthesis, decreased cholesterol uptake and efflux, and lipid deposition in renal tubules 111 , indicating that PACS2 is a major regulator in lipid-related kidney lesions in DKD. These studies suggested that MAM-related proteins played key roles in regulating lipid deposition in DKD, but more research is needed to elucidate the molecular mechanism of MAM involvement in EFD in DKD.…”
Section: The Role Of Mam In Dkdmentioning
confidence: 99%